Green Marketing and Its Impact on Consumer Purchase Decision in Circular Economy. A Systematic Literature Review - Adhikari, Sujita; Ojha, Deepak; Poudel, Hemkanta (Janaprakash Journal of Multidisciplinary Research, 2025)
The Study on consumer purchasing decisions, green marketing, and the circular economy which are published between the year 2015 and 2025. Thematic analysis, keyword co occurrence mapping, and descriptive statistics were used to analyze 65 articles which were taken from Scopus. The annual distribution shows increase in publications after 2020, with 2024 and 2025 recording the highest articles, which indicates a growing global focus on sustainability. Whereas, predominance of Quantitative studies indicates a strong interest in measuring consumer attitudes and behavioral outcomes. Country-wise analysis reveals widespread international contributions but citation impact seems to be more concentrated in countries such as the United Kingdom and Hungary. And Sustainability (Switzerland) journal seems to be the leading sources of publication and citations. Through keywords co-occurrence analysis three themes have been identified sustainability, marketing, and consumption behavior, consumer attitudes, perceptions, and digital influence, and green marketing strategies and sustainable consumption. In order to increase consumer trust and green purchase intentions, credible and transparent sustainability communication is vital. Studies also show that digital platforms play an important role in influencing consumers about sustainability but, green washing remains a major barrier, weakening consumer confidence and widening the attitude behavior gap. Thus, the review shows authenticity, clear communication, and integration of circular economy practices are important for effective green marketing strategies. This review highlights that businesses, policymakers, as well as researchers need to promote sustainable green consumption and should strengthen environmental responsibility.